APPRAISAL OF THE TESTAMENTARY FREEDOM OF A TESTATOR UNDER ISLAMIC LAW: A COMPARATIVE ANALYSIS - Liman, Abdullahi N Liman; Zanwa, Ahmed Aliyu (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
Will (Bequest) is a branch of Islamic inheritance system which deals with the freedom of a testator dispose of his property. This study undertakes a comparative analysis of the testamentary freedom of a testator under Islamic law, wills laws and other jurisdictions of interest, examining the extent to which a testator can as of right dispose of his property upon death. The Islamic inheritance system, offers two major restriction to a testator when making a Will (bequest). A testator under Islamic inheritance law is restricted to dispose of his property to the maximum of 1/3 and he/she is not allowed to write a Will (bequest) in favour of his/her heirs so as to ensure the rights of legal heirs and other beneficiary are protected. The research work reveals a significant differences in the approaches of testamentary freedom. The Nigeria Wills laws, the Act and other administration of estates laws of some states allowed a testator with a testamentary as well as a complete freedom to dispose of all his property to anybody of his own choice. The testator’s powers are constructively truncated by certain customary laws and rules in Nigeria.  A comparative understanding and examination of the laws of the United Kingdom, India, Ghana and some Arab nations, highlights the diverse ways in which testamentary freedom is regulated and balanced for the purpose of ensuring that a testator, adhered to the Will laws for the purpose of protecting all and sundry in the estate distribution and management.  The research also contributes to a deeper understanding of the complexities of testamentary freedom and its implication for Muslim testators who live and die in an environment that the Islamic law of inheritance (Will) does not adhere to.